Implementasi Akad Mudharabah dan Musyarakah pada Perbankan Syariah dalam Perspektif Fatwa DSN-MUI: A Systematic Literature Review - Moh. Asep Zakariyah Ansori; Roisiyatin Roisiyatin; Dhio Novriyansa Gunawan; Reva Mardiana; Rizkia Rahmadianti; Viri Alviorita (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study examines the implementation of mudharabah and musyarakah contracts in Islamic banking in Indonesia, based on DSN-MUI Fatwa No. 07 and No. 08 of 2000. This study uses the Systematic Literature Review (SLR) method following PRISMA guidelines, searching the Garuda and Google Scholar databases. From 50 articles found, 13 scientific journal articles were analyzed (2019–2025), supported by 9 reference books and 1 official data source (OJK, 2024). Data were analyzed using thematic synthesis to identify patterns and differences between studies. Four main themes were found: fatwa compliance, moral hazard, sharia financial literacy, and risk supervision. Mudharabah generally complies with the fatwa but still faces challenges such as side streaming and limited human resources. Musyarakah still shows inconsistencies in profit-sharing mechanisms and bank involvement. This study offers a thematic synthesis and a conceptual framework on compliance factors not widely found in previous research. This study recommends strengthening the Sharia Supervisory Board's role, improving human resource competence, and developing more detailed technical guidelines.